2012
DOI: 10.2147/ijgm.s25989
|View full text |Cite
|
Sign up to set email alerts
|

Update on the clinical utility and optimal use of cefditoren

Abstract: This article reviews and updates published data on cefditoren. The in vitro activity of cefditoren and its potential pharmacokinetic/pharmacodynamic adequacy to cover emerging resistance phenotypes in the present decade is reviewed. Cefditoren’s in vitro activity against most prevalent bacterial respiratory pathogens in the community and its pharmacokinetic/pharmacodynamic profile suggests a significant role for cefditoren in the treatment of respiratory tract infections. Clinical trials (in acute exacerbation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Several studies have demonstrated both the effectiveness and safety of these drugs in this population, also in comparison with fluoroquinolones 2125. Among the cephalosporins, cefditoren pivoxil, an oral, β-lactamase-stable, expanded-spectrum cephalosporin, was shown to have good in vitro activity not only against methicillin-susceptible Staphylococcus aureus , Streptococcus pyogenes , Streptococcus pneumoniae , including penicillin-resistant strains, but also against H. influenzae and M. catarrhalis ,2631 with minimum inhibitory concentrations of 90% for AECB isolates that are lower than those for other oral cephalosporins,22 and its clinical efficacy and safety have been well established 32–35. In comparative studies with cephalosporins, levofloxacin was demonstrated to be more favorable in the treatment of AECB21,24,36 but, to the best of our knowledge, no trial has been conducted comparing cefditoren and levofloxacin.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated both the effectiveness and safety of these drugs in this population, also in comparison with fluoroquinolones 2125. Among the cephalosporins, cefditoren pivoxil, an oral, β-lactamase-stable, expanded-spectrum cephalosporin, was shown to have good in vitro activity not only against methicillin-susceptible Staphylococcus aureus , Streptococcus pyogenes , Streptococcus pneumoniae , including penicillin-resistant strains, but also against H. influenzae and M. catarrhalis ,2631 with minimum inhibitory concentrations of 90% for AECB isolates that are lower than those for other oral cephalosporins,22 and its clinical efficacy and safety have been well established 32–35. In comparative studies with cephalosporins, levofloxacin was demonstrated to be more favorable in the treatment of AECB21,24,36 but, to the best of our knowledge, no trial has been conducted comparing cefditoren and levofloxacin.…”
Section: Introductionmentioning
confidence: 99%